Educação socioambiental e letramento imagético: docentes e os livros didáticos de Ciências de uma escola rural em comunidade quilombola feirense - Nascimento, Carine de Jesus (2023)
The study on teachers' conceptions and practices involving image literacy is justified by the relevance of the theme in the social, political and academic scope. It is essential to investigate, know and understand the issue of image literacy and its peculiarities in the school environment. The present work aimed to understand how teachers of the early years of elementary school in a public school in the rural area of Feira de Santana conceive and use the image literacy about the Environment in science books. The study is anchored in the debate of the teaching practice, environmental issues, textbooks and image literacy in a qualitative research, of the study of case type. The locus was a school in the early years of elementary school located in a quilombola community in the rural area of Feira de Santana. The subjects participating in this research were the director and five teachers: one from the first year, one of the third year, one from the fourth year and two from the fifth year. The data collection instrument was the questionnaire and the data was investigated based on the French discourse analysis created by Pêcheux. From the data produced, it was evident the relevance of a cautious and critical point of view by the teachers towards the curricular norms and guidelines of national public policies for the use of images about the Environment in Science textbooks. It was possible to perceive that the State University and the Departments of Education and Environment in the city of Feira de Santana, when promoting socio-environmental actions in the city space, collaborate with the school institutions, including those in rural areas. The socio-environmental mobilization practices promoted by members of the Candeal II Community Development Association, where the researched school is located, also provide opportunities for the cultural and socio-environmental strengthening of the community. The teachers recognize that the educational institution is located in a rural quilombola community, with physical elements and lifestyles different from the urban area of Feira de Santana, where they live. They are also concerned with providing classes that deal with environmental issues, using images displayed through various printed and virtual media, with few teachers revealing to stay restricted to the Science textbook, when addressing the theme Environment. These professionals conceive the Environment as the space where natural elements are found, calling attention to the human presence in that place. They also demonstrated a good understanding of image literacy, that is because they consider the image an essential instrument for children's learning, with the possibility of developing better understandings about the environmental topic and about characteristics of the local environment. In view of what some of the teachers reported, the educational work proposed by them is at the level of image literacy, because they encourage discussions that lead the students to associate details of images inserted in the Science textbooks with typical circumstances of the quilombola community where they live. This study enabled still-initial discussions about science teaching in the early years of Elementary School, emphasizing the potential of promoting articulations between the scientific knowledge and the student reality.